THE INHERITANCE AND EXISTENCE OF THE TRAE WONG BAND IN BANG LEN DISTRICT NAKHON PATHOM PROVINCE - Phothikawin, Dhanyaporn (Mahidol Music Journal, 2023)
This research aimed to 1) study the history of the Trae Wong Band in Bang Len District Nakhon Pathom Province, 2) study the condition and problems of the Trae Wong Band in Bang Len District Nakhon Pathom Province, and 3) study the inheritance and existence of the Trae Wong Band in Bang Len District Nakhon Pathom Province. This research used the qualitative research method, which consisted of the key informants as follows: 1) people who had knowledge and understanding of the history, condition, problems, inheritance, and existence of the Trae Wong Band in Bang Len District Nakhon Pathom Province. 2) Professional musicians who were related to the Trae Wong Band in Bang Len District Nakhon Pathom Province. The research results were presented in a descriptive research method. The results found that 1) the history of the Trae Wong Band, started with music teachers and musicians in 4 Provinces: Teacher Thongdee Dechaona, teacher and musician from Nakhon Pathom Province; Teacher Dawei Tassananate, teacher and musician from Ratchaburi Province; teachers and musicians from Amphawa District, Samut Songkhram Province; and Teacher Boonrawd Thongkamsai, Teacher Prakong Wisuthiwong, and Teacher Thanu Wisuthiwong, teachers and musicians from Song Phi Nong District Suphanburi Province. They inherited their knowledge to the Trae Wong Band as follows: Wichian Entertain Band, Bantoengsilp Band, Kwanjai Silamull Band, and Siam Poolsilp Band. 2) The condition and problems of the Trae Wong Band, it was caused by the inheritance of knowledge and management. The external condition and problems of the Trae Wong Band, it was caused by social and cultural conditions, technology, economy, and health. 3) the inheritance and existence of the Trae Wong Band in Bang Len District Nakhon Pathom Province, were caused by internal family knowledge and external knowledge inheritance. Adaptation of the Trae Wong Band consisted of the application of musical instruments and modern music performance, uniqueness creation, marketing; public relations; and recognition, and appreciation of the Trae Wong Band in terms of traditions and rituals.